Social Image of the Ural Region Mining Workers at the Post-Reform Time Period - Korobkov, Yurii D. (2020)
The article dwells upon a transition character of the Ural proletariat at the post-reform time period. Both domestic and foreign historiography define the social image of the Russian worker of the 20th century second part as either proletarian or referring to a “half-worker and half-peasant” type, combining traditional pre-capitalist features with newer ones, characteristic of industrial manufacture. A manufacturer’s being connected to the land as well as forming a certain mentality combined with the professional skills are considered the main criteria while defining the Russian workers’ typology. Taking into consideration the Urals old tradition of industrial manufacture, the process of forming an independent class at the area progressed rather vigorously. Despite of land allotments availability, workers in the Urals got under influence of modernization. Treating scornfully peasant work, industrial workers purposefully separated themselves from peasants. Nevertheless, it will be wrong to speak about complete disappearance of traditional peasant psychology among the Ural proletariat of the said time period. The working class at the region used to belong to a transition type, therefore we can speak about its incomplete establishment as a bourgeois society class.